Budget Performance Analysis at LLDIKTI Region II Work Unit Based on Budget Implementation Indicators - Mintareza, M.; Fitriasuri, Fitriasuri (International Journal of Finance Research, 2025)
The Budget Implementation Performance Indicator is an instrument used to monitor and evaluate the implementation of the budget of the Ministry/Institution work unit. The Budget Implementation Performance Indicator has 3 aspects, namely the quality aspect of budget planning, the quality aspect of budget implementation, and the quality aspect of budget implementation results. The indicators consist of eight components, namely the revision of DIPA, deviation from page III of DIPA, budget absorption, contractual spending, bill settlement, management of inventory and additional supply funds, dispensation of baiya warrants, and output achievements. LLDIKTI Region II as a work unit under the Ministry of Higher Education, Culture, Research and Technology plays an active role in the implementation of monitoring and evaluation with Budget Implementation Performance Indicators in measuring whether the budget implementation is good or not in the work unit which will later have an impact on the efficiency and effectiveness of budget use.